Pelaksanaan Tugas-Tugas Apron Movement Control Dalam Keterbatasan Jumlah Personil Di Bandar Udara Internasional Raja Haji Fisabililah Tanjungpinang - Tita Ervinda Taebenu; Teguh Ariebowo (Student Research Journal, 2023)
Raja Haji Fisabililah International Airport is an airport located in the city of Tanjungpinang, Riau Islands. One of the work units that support the smoothness and safety of flights at Raja Haji Fisabilillah Airport is the Apron Movement Control (AMC). This research was conducted to find out how the regularity of the implementation of the tasks of the Apron Movement Control unit in the midst of limited personnel. This research uses qualitative research methods and was conducted from August to September 2022 at Raja Haji Fisabilillah Airport using primary data and secondary data. Primary data is data obtained directly through observation and interviews while secondary data is data obtained through documents based on triangulation of techniques and triangulation of sources, such as interviews, observation, and documentation. The results of this study are the discovery of problems in the form of no personnel who carry out supervision/controlling on a permanent basis on the air side during aircraft arrivals and there are no AMC personnel who have marshalling certification/guiding aircraft parking on the apron, because according to the applicable SOP, one of the AMC personnel at each branch office is required to have marshalling certification. Therefore, AMC personnel provide the results of the performance evaluation of each personnel and the weekly work draft periodically to PT Angkasa Pura II, that with the condition of limited personnel, the AMC unit gets a solution from the facilitator of Raja Haji Fisabilillah Airport, namely PT Angkasa Pura II.